Improvement of High‐Density Lipoprotein Function in Patients With Early Rheumatoid Arthritis Treated With Methotrexate Monotherapy or Combination Therapies in a Randomized Controlled Trial. Issue 1 (January 2017) - Charles‐Schoeman, Christina; Yin Lee, Yuen; Shahbazian, Ani; Wang, Xiaoyan; Elashoff, David; Curtis, Jeffrey R.; Navarro‐Millán, Iris; Yang, Shuo; Chen, Lang; Cofield, Stacey S.; Moreland, Larry W.; Paulus, Harold; et al.
Abstract : Objective: Abnormal function of high‐density lipoprotein (HDL) has been implicated as a potential mechanism for the increased incidence of cardiovascular (CV) disease in patients with rheumatoid arthritis (RA). This study was undertaken to evaluate changes in HDL function and HDL‐associated proteins over 2 years of follow‐up in patients with early RA receiving either methotrexate (MTX) monotherapy, MTX + etanercept (ETN) combination therapy, or MTX + sulfasalazine (SSZ) + hydroxychloroquine (HCQ) triple therapy in the Treatment of Early Aggressive Rheumatoid Arthritis (TEAR) trial. Methods: The antioxidant capacity of HDL, paraoxonase 1 (PON‐1) activity, and levels of HDL‐associated haptoglobin (Hp), HDL‐associated apolipoprotein A‐I (Apo A‐I), and myeloperoxidase (MPO) were measured in 550 TEAR participants at 4 time points (time 0 [pretreatment] and at 24, 48, and 102 weeks of treatment). Repeated‐measures analysis using mixed‐effects linear models with an autoregressive covariate structure was performed to model the within‐subject covariance over time. Results: Mixed‐effects models, which were controlled for traditional CV risk factors, treatment regimen, prednisone use, and statin use, demonstrated significant associations between RA disease activity, measured using the Disease Activity Score in 28 joints, erythrocyte sedimentation rate, or C‐reactive protein level, and the profile of HDL function over time. Specifically, decreases in RA disease activity over time were associated with increases in PON‐1 activity and levels of HDL‐associated Apo A‐I, and decreases in the HDL inflammatory index and levels of MPO and HDL‐associated Hp. Conclusion: Reduced disease activity in patients with early RA treated with MTX monotherapy, MTX + ETN combination therapy, or MTX + SSZ + HCQ triple therapy in the TEAR trial was associated with improvements in the HDL function profile. Additional studies are warranted to evaluate abnormal HDL function as a potential mechanism and therapeutic target for CV risk in patients with RA.